Are Established Methods of Physiotherapeutic Management for Long‐term Neurological Conditions Applicable to 'Orphan' Conditions such as Syringomyelia?. (4th December 2014) - Smith, Rebecca; Jones, Gareth; Curtis, Alexandra; Murphy, Hollie; Flint, Graham
Abstract: Background and Purpose: Syringomyelia is a rare or 'orphan' condition with the potential to cause significant disability and detrimental effects to quality of life. Syringomyelia shares similar symptoms to those common in other long‐term neurological conditions, including spinal cord injury and multiple sclerosis. In these more prevalent conditions, physiotherapy is utilized widely and is effective in optimizing physical, psychological and social parameters. Therefore, we theorized that physiotherapy might be transferable to, and beneficial to syringomyelia patients. As a paucity of literature exists in this area, we aimed to evaluate the existing uptake and perceived efficacy of physiotherapy. Methods: An exploratory, mixed methodology was selected to derive sufficient qualitative data for analysis. Specifically designed questionnaires and semi‐structured interviews yielded data on uptake and perceived physiotherapy efficacy. One hundred patients from a National Health Service tertiary syringomyelia service were invited to participate. Results: The questionnaire and interviews were completed by 49 and 20 patients, respectively. Of the small number of patients receiving physiotherapy, the majority reported beneficial effects on pain modulation and quality of life. Stretching and hydrotherapy were deemed effective for relief of pain and stiffness. Additionally, physiotherapy was reported to provide similar benefits to surgical intervention. Discussion: Syringomyelia patients report physiotherapy to provide benefits for symptom management and quality of life. Such findings suggest that established rehabilitation techniques in more common conditions may be transferable to those less prevalent. Uptake of physiotherapy was limited, seemingly because of inadequate information, knowledge and resources. To address these deficiencies, further studies should be planned investigating the effectiveness of physiotherapy modalities, such as hydrotherapy, in parallel or in conjunction with surgery and/or pharmacology. Additionally, syringomyelia could be represented alongside similar pathologies in research trials to initiate further research questions and drivers for funding. Copyright © 2014 John Wiley & Sons, Ltd.